Magneto‐Controlled Biocatalytic Cascades with Logically Processed Input Signals – Substrate Channeling versus Free Diffusion. Issue 22 (19th October 2018) - Filipov, Yaroslav; Zakharchenko, Andrey; Minko, Sergiy; Katz, Evgeny
Abstract: Magnetic nanoparticles (MNPs) functionalized with various enzymes (amyloglucosidase, glucose oxidase and horseradish peroxidase) were used to perform biocatalytic cascades in two different states, solute suspension or aggregated, produced in the absence or presence of an external magnetic field. The biocatalytic reactions proceeded through bulk solution diffusion of intermediate substrates or substrate channeling, when the systems were dispersed or aggregated, respectively. The both pathways have shown very similar kinetics, unless the intermediate substrate was consumed by an additional biocatalytic process called "filter" for brevity. In the presence of the "filter" process, the diffusional process in the bulk solution was significantly inhibited, while the process based on the substrate channeling was still active. The systems were switched reversibly between the inhibited dispersed state and the active aggregated state by removing and applying the external magnetic field, respectively. The signal‐controlled biocatalytic cascades were considered as Boolean logic circuits with the inputs consisting of biomolecules and the magnetic field on‐off. Abstract : Magnetic nanoparticles (MNPs) functionalized with various enzymes (amyloglucosidase, glucose oxidase and horseradish peroxidase) are used to perform biocatalytic cascades in two different states – solute suspension or aggregated – produced in the absence or presence of an external magnetic field. The biocatalytic reactions proceed through bulk solution diffusion of intermediate substrates or substrate channeling when the systems are dispersed or aggregated, respectively. The signal‐controlled biocatalytic cascades are considered as Boolean logic circuits with the inputs consisting of biomolecules and the magnetic field on‐off.